Hermes’ Commerce: An essay on Translation and Hermeneutics - Grassi, Martin (Theoria and Praxis: International Journal of Interdisciplinary Thought, 2016)
The question on the art of translation concerns the very essence of Hermeneutics, for comprehension is always a way of translating the world of the other to whom I am listening or reading. The mythological figure of Hermes will lead the way to acknowledge the ambiguities and paradoxes implied in translating and, therefore, in hermeneutics. The necessity of keeping at the same time the distance and the proximity between our world and the foreign one, has taken us to present the idea of commerce as the central activity in every interpretation. On the other hand, interpretation implies also a common World-Life (Lebenswelt), reconsidering the notion of objectivity, without loosing, however, the linguistic dimension of human experience. We will show, in dialogue with Paul Ricoeur, how a meditation on translation impacts the very core of an hermeneutical philosophy.